Clinical otology - Pensak, Myles L.; Choo, Daniel I. (New York : Thieme, 2015)
'This text represents an excellent summary of the current state of knowledge in otology. This text is strongly recommended as a primer in otology for residents. Practicing otolaryngologists and otologists will find it a useful review. The text's up-to-date contributions and references offer an excellent resource even for the experienced otologist. Otology and Neurotology Clinical Otology, Fourth Edition, is a detailed, contemporary review of diagnostic and therapeutic options for patients with otologic and related disorders. It addresses basic science, the clinical application of therapeutics in otology, and current research, and is designed to help physicians make the best decisions in managing the care of their patients. Key Features: New chapters on molecular genetic diagnostics, contemporary management of external and internal hearing devices, and vestibular and audiologic neuro diagnostics More than 150 high-quality, color illustrations clarify key concepts presented in the text Covers the current clinical application of genetics and contemporary testing for hearing loss'--Publisher's description.
Part 1: Basic science. Anatomy and embryology of the ear -- Principles of clinical audiology and assessment of auditory physiology -- Vestibular physiology -- The eustachian tube -- Molecular biology of the inner ear -- Pharmacology of otologic drugs -- Part 2: Evaluation. Temporal bone imaging -- Diagnostic audiology -- Assessment of auditory processing disorders -- Laboratory tests of vestibular and balance functioning -- Clinical evaluation of the cranial nerves -- Otologic photography and videography -- Clinical evaluation of hearing loss -- Evaluation of the dizzy patient -- Part 3: Management. Disorders of the auricle -- Diseases of the external auditory canal -- Aural atresia and unilateral hearing loss -- Otitis media -- Chronic otitis media -- Complications of otitis media -- Otosclerosis -- Temporal bone trauma -- Hereditary hearing impairment -- Nonhereditary hearing loss -- Benign neoplasms of the temporal bone -- Cystic lesions of the petrous apex -- Malignant tumors of the temporal bone -- Vestibular disorders -- Facial nerve disorders -- Immunologic disorders of the inner ear -- Part 4: Rehabilitation. Adult audiological rehabilitation -- Implantable hearing devices -- Cochlear implants and auditory brainstem implants -- Rehabilitation of peripheral vestibular disorders -- Rehabilitation and reanimation of the paralyzed face -- Otalgia -- Evaluation and management of pulsatile tinnitus -- Theory and treatment of tinnitus and decreased sound tolerance -- Medical-legal aspects of otology.
Includes bibliographical references and index.
Preceded by: Clinical otology / [edited by] Gordon B. Hughes, Myles L. Pensak. 3rd ed. 2007.
Description based on online resource; title from electronic title page (R2 Digital Library, viewed January 24, 2019).
Master record variable field(s) change: 050
Keywords: Ear -- Diseases; Otology; Hearing disorders; Ear Diseases; Ear -- physiology; Hearing Disorders